Exercise with food withdrawal at thermoneutrality impacts fuel use, the microbiome, AMPK phosphorylation, muscle fibers, and thyroid hormone levels in rats. Issue 3 (7th February 2020) - Giacco, Antonia; delli Paoli, Giuseppe; Simiele, Roberta; Caterino, Marianna; Ruoppolo, Margherita; Bloch, Wilhelm; Kraaij, Robert; Uitterlinden, André G.; Santillo, Alessandra; Senese, Rosalba; Cioffi, Federica; Silvestri, Elena; et al.
Abstract: Exercise under fasting conditions induces a switch to lipid metabolism, eliciting beneficial metabolic effects. Knowledge of signaling responses underlying metabolic adjustments in such conditions may help to identify therapeutic strategies. Therefore, we studied the effect of mild exercise on rats submitted to food withdrawal at thermoneutrality (28°C) for 3 days. Animals were housed at thermoneutrality rather than the standard housing temperature (22°C) to avoid beta‐adrenergic signaling responses that themselves affect metabolism and well‐being. Quantitative analysis of multi‐organ mRNA levels, myofibers, and serum metabolites shows that this protocol (a) boosts fat oxidation in muscle and liver, (b) reduces lipogenesis and increases gluconeogenesis in liver, (c) increases serum acylcarnitines (especially C4 OH) and ketone bodies and the use of the latter as fuel in muscle, (d) increases Type I myofibers, and (e) is associated with an increased thyroid hormone uptake and metabolism in muscle. In addition, stool microbiome DNA analysis revealed that food withdrawal dramatically alters the presence of bacterial genera associated with ketone metabolism. Taken together, this protocol induces a drastic switch toward increased lipid and ketone metabolism compared to exercise or food withdrawal alone, which may prove beneficial and may involve local thyroid hormones, which may be regarded as exercise mimetics. Abstract : Environmental temperature influences metabolic responses. The results of the present study show that the relatively mild metabolic effects of exercise at thermoneutrality are boosted when combined with food withdrawal. To our knowledge, this is the first study to reveal this, studying the whole animal's response ranging from microbiota to muscle, liver, and serum, suggesting a contributing role for thyroid hormone.